A comprehensive review of GABA in autism spectrum disorders: associations, mechanisms, and therapeutic implications - Wang, Peng; Sun, Jin (Frontiers in Psychiatry, 2025)
The etiology and pathogenesis of Autism Spectrum Disorder (ASD) are not yet clear. Gamma-aminobutyric acid (GABA), as an inhibitory neurotransmitter in the brain, is closely related to the pathogenesis of ASD. Animal models and clinical studies of ASD suggest that abnormalities in GABAergic neurons, signaling pathways, and related genes may play an important role in the pathogenesis of ASD, leading to abnormal levels of GABA in the blood and brain tissue of individuals with ASD. Additionally, GABAergic drugs have shown potential to improve ASD symptoms in animal models, but their efficacy and safety in clinical use still need further research. Therefore, this article reviews the relationship between GABA and ASD, as well as the related research on GABA levels and drug treatment, to further explore the pathogenesis of ASD and provide a theoretical basis for the diagnosis and treatment.